A criminalidade em Manaus: um estudo segundo os casos de prisão em flagrante, no período de 2014-2015 - Freires, Metusael Farias (2016)
The general objective of this study was to analyze the crime in the city of Manaus, through a qualitative and quantitative research. Therefore, the following specific objectives have been built: contextualize the problem of crime in Manaus, situating it within a national context; identify criminal types of higher recurrence, present in cases of arrest in flagrant delicto, tilled in flagrant bases of the Civil Police of Amazon, in Manaus, in the period 2014 - 2015; and analyze crime in Manaus, presenting an overview for the years 2014 and 2015, through arrests in flagrante delicto. In tangent to methodology, the survey was processed qualitatively and quantitatively, as the data in a deductive analysis. The main database were the reports of the Department of Police Enforcement, of the Civil Amazon Police and SISP, Public Security System Information, used by the civil police for registration of police occurrences. The data were grouped by Integrated Police District – IPD, by district of Manaus and finally, the data were grouped, forming a basis for Manaus. As a result, among other things, the data showed that crime in Manaus has high numbers of trafficking offenses and theft, added to others reflect the uncertainty perceived by the Manauara population. However, among the many observed crimes, few have a significant percentage of arrests. During the research a major difficulty was the formation of the data list due to lack of standardization of the information contained in the reports of the Department of Police Activities of the Civil Police of Amazonas. In conclusion, can be said that exist a few criminal types with high incidence in the Amazon capital, but they are present in all areas. However, the need for investment in the public safety field is large and cannot be limited to purchase of vehicles and personnel hiring. Investing in research is a constant need, especially for the improvement of practices and the introduction of new public policies to face the increase and proliferation of criminal practice.